Effects of flower age on pollination success in Lepanthes sanguinea - Guevara Ramos, Edwin; Agosto Pedroza, María M.; Tremblay, Raymond L. (Lankesteriana: International Journal on Orchidology, 2016)
The effect of flower age on pollination has been shown to be important in promoting cross pollination when the sexual expression of flowers is age depen- dent (Ackerman 1975, Singer & Koehler 2002).